Biosimilar infliximab for the management of rheumatoid arthritis in France: what are the expected savings?. Issue 2 (24th March 2016) - Beck, M; Michel, B; Rybarczyk-Vigouret, M-C; Sordet, C; Sibilia, J; Velten, M
Abstract : Objectives: Biosimilar infliximab, the first similar biological medicinal product containing monoclonal antibodies to be commercialised, is likely to contribute to a significant reduction in healthcare costs. We aimed to assess the cost savings potential over 1 year of the use of biosimilar infliximab for the treatment of rheumatoid arthritis (RA) patients in Alsace and in France, in a real-life setting. Methods: The analysis was based on a previously conducted observational study which evaluated the annual cost of the care of patients with RA treated with biological therapies in 2012 in Alsace. Average annual costs to manage RA patients were calculated, taking into account the decrease in the retail price between 2012 and 2015 (as given in the official national price list) and the local negotiated price for biosimilar infliximab. Annual cost savings for different biosimilar prescription scenarios were calculated using 2015 prices. Results: Management of RA patients with biosimilar infliximab was significantly cheaper than with adalimumab or etanercept (€11 907 vs €12 981 and €13 551, respectively). The projected annual cost savings reached €13.6 million nationally, if all adult RA patients treated with the originator infliximab switched to the biosimilar drug. These savings, if fully reallocated for the treatment of RA, would enable the treatment of 1141 additional patients. Conclusions: The study showed a positive financial impact of introducing biosimilar infliximab for the treatment of RA patients in France. Such savings could contribute to improved patient care by allowing more patients to be treated without more money being spent.